The role of e-government in reducing corruption: A systematic review - Ni Wayan Rustiarini (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
A number of studies state that e-government is a "powerful" anti-corruption tool but other researchers still have doubts about the role of e-government. In fact, other researchers claim that e-government is not only a powerful weapon against corruption but also has the potential to create corruption opportunities. Starting from this phenomenon, this study aims to synthesize research results regarding the role of e-government in reducing corruption. This research systematized the results of research over the past 19 years using a systematic review method. This method provides a comprehensive review so it is expected to reduce the bias of literature. This paper reviews 16 articles published in reputable peer-reviewed journals. Most articles use macro-comparative data in all countries, while other articles use surveys, case studies, and conceptual papers. In general, the systematic review result show that e-government can reduce corruption. However, the success of e-government is not universally applicable. There are internal and external organizational factors that influence the effectiveness of e-government functions to againts corruption.